Production and Characterization of Nutrients from Ecoenzymes Based on Fruit Waste and Green Vegetable Waste - Ashari, Asri Mulya; Apindiati, Rita Kurnia; Amir, Amir; Dirhana, Dirhana; Amran, Arman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Ecoenzymes are fermented products of organic waste such as fruit and green vegetables, which are rich in nutrients so they have great potential as organic fertilizer. Making ecoenzymes can reduce waste discharge into the environment, thereby reducing pollution, thus supporting environmentally friendly sustainable agricultural practices. This research aims to produce and characterize the macro nutrient content of Nitrogen (N), phosphorus (P), Potassium (K) and organic C from ecoenzymes produced from pineapple and green vegetable waste. Organic waste from pineapple skins and green vegetables is fermented with palm sugar and water in a ratio of 3: 1: 10 (organic material: sugar: water), in a container with a lid for 3 months. The process of observing changes in pH per week was carried out during the fermentation process. Determination of the macro nutrient content of organic N, P, K and C from ecoenzymes produced from pineapple and green vegetable waste using the atomic absorption spectrophotometry method. The research results showed that the organic N, P, K and C contents were 9.5%, 3.01%, 1.02% and 21.04%, respectively.